BIODIVERSITAS IKAN LUBUK LARANGAN SUNGAI KAITI DI ROKAN HULU PROVINSI RIAU - Desi Wulandari; Prima Wahyu Titisari (UIN Sunan Gunung Djati Bandung, 2023)
Indonesia is one of the biodiversity countries, Indonesia ranks the second largest biodiversity in the world after Brazil. Around 8500 fish species are in Indonesian waters, as many as 1300 fish species occupy the fresh waters of western Indonesia. This is inseparable from the role of the community who strives to protect and preserve the environment. One of the efforts to conserve freshwater fish by the community is the existence of a prohibition pit. The purpose of this study was to explore the biodiversity of fish species in the river basin and its management. The method in this study is a survey method with a qualitative descriptive approach. Collecting data in the form of primary data, through observation and interviews. Sampling of fish is through sampling directly to the location. The research was conducted from April 2021 to July 2021. From the results of the study found 9 species of fish, namely: Sebarau (Hampala sp), Lampam (Barbonymus schwanenfeldii), Selais (Kryptopterus cryptopterus), Gabus (Channa striata), Baung (Mystus temarus), Limbat (Clarias nieuhofii), Seluang Juo (Luciosoma trinema), Nila (Oreochromis niloticus), and Toman (Channa micropletes). The most widely used fish by the community are lampam, sebarau and cork fish. While the rare fish are toman fish and limbat fish. To maintain the preservation of fish, people are not allowed to take fish before the harvest period and can only take large fish. The harvest is done the day before the month of Ramadhan. The regulation aims to maintain the existence of local fish.